THE EFFECTIVENESS OF MIND MAPPING TECHNIQUE TO TEACH STUDENTS’ SPEAKING ABILITY AT THE TENTH GRADE STUDENTS OF SMAN 1 JATIWANGI IN THE ACADEMIC YEAR 2017/2018 - Irfan Afriansya (Universitas Majalengka, 2019)
This article discusses The Effectiveness of Mind Mapping Technique to Teach Students’ Speaking Ability at the Tenth Grade Students of SMAN 1 Jatiwangi. The purpose of this research is to reveal the effectiveness of mind mapping technique to teach students’ speaking ability at the tenth-grade students of SMAN 1 Jatiwangi in the academic year 2017/2018. The researcher used pre-experimental one group pre-test post-test design. The population of this research is the tenth-grade students of SMAN 1 Jatiwangi. Cluster random sampling is used to determine the sample. The sample of this study is X MIPA 1 which consists of 36 students. The treatment was conducted three times by using the mind mapping technique. The result of the study showed that the average score of pre-test was 8,9 and the average score of post-test was 13,3. The tobserve was found to be 11,5 and the tcritical was 2,03. It showed that tobserve was higher that tcritical which meant there was a significant effect to teach students' speaking ability by implementing the mind mapping technique. In conclusion, the mind mapping technique is effective to teach students’ speaking ability at the tenth-grade students of SMAN 1 Jatiwangi. The researcher suggests the teacher to applicate mind mapping technique in teaching students’ speaking ability.